Selective up-regulation of dopamine D1 receptors in dendritic spines by NMDA receptor activation - Scott, Lena (The National Academy of Sciences, 2002)
Glutamate, by activating N-methyl-d-aspartate (NMDA) receptors, alters the balance between dopamine D1 and D2 receptor signaling, but the mechanism responsible for this effect has not been known. We report here, using immunocytochemistry of primary cultures of rat neostriatal neurons, that activation of NMDA receptors recruits D1 receptors from the interior of the cell to the plasma membrane while having no effect on the distribution of D2 receptors. The D1 receptors were concentrated in spines as shown by colocalization with phalloidin-labeled actin filaments. The effect of NMDA on D1 receptors was abolished by incubation of cells in calcium-free medium and was mimicked by the calcium ionophore ionomycin. Recruitment of D1 receptors from the interior of the cell to the membrane was confirmed by subcellular fractionation. The recruited D1 receptors were functional as demonstrated by an increase in dopamine-sensitive adenylyl cyclase activity in membranes derived from cells that had been pretreated with NMDA. These results provide evidence for regulated recruitment of a G protein-coupled receptor in neurons, provide a cell biological basis for the effect of NMDA on dopamine signaling, and reconcile the conflicting hyperdopaminergic and hypoglutamatergic hypotheses of schizophrenia.